Kelayakan Multimedia Interaktif dengan Adobe Animate CC pada Materi Pencernaan Makanan - Puspita, Farah; Ningsih, Kurnia; Wahyuni, Eko Sri (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the validity and reliability of interactive multimedia with Adobe Animate CC on food digestion material. The research method used is Research and Development (R&D), with a 3-D development model, which includes defining, designing, and developing. The research instrument used was a validation sheet with aspects of assessing the feasibility of material content, linguistic aspects, presentation aspects and aspects of interactive multimedia characteristics. Validation was carried out by 5 validators selected by purposive sampling by considering that the validator is an expert in the field of education and media, especially technology-based media. Media assessment is done qualitatively through a checklist assessment which is then converted into a quantitative value with Likert scale provisions. The validation data obtained from the validator's assessment was then analyzed using the Aiken validation analysis technique and its reliability was measured using the intra-class correlation coefficient. The validation results showed that the interactive multimedia was declared valid with an average validation score of 0.93 with 5 Likert scales. The reliability test results with the SPSS Statistic program obtained a value of 0.788 which shows excellent reliability. Thus, it can be concluded that this interactive multimedia is valid and suitable for use in learning.